Bilateral staghorn renal calculi - Melani Limenco Benly; Melly Liman (Institute of Computer Science (IOCS), 2023)
Staghorn calculi are large renal stones that occupy most or all of the renal collecting system. The prevalence of kidney stone disease is estimated at 1% to 15%, varying according to age, gender, race, and geographic location. Although kidney stones are more common in men, staghorn stones occur less often in men and are usually unilateral. Patients with bilateral staghorn calculi might be unique and have complex clinical problems. Meanwhile, complete renal function loss in 50% of affected kidneys can occur after two years without treatment. Case presentation: A patient is a 69-year-old man who was brought to the Emergency Department for bilateral flank pain, with a referral from RSUD Bogor, due to a bilateral staghorn kidney stone. After further examinations, BNO indicated the bilateral nephrolithiasis and laboratory tests with abnormal blood glucose, ureum level, gas, urine leukocyte, and erythrocyte. The patient was then provided medications and experienced right nephrolithotomy.